The Effect of IFRS 15 Mandatory Adoption on Earnings Management: Evidence from Firms Listed on The STOXX Europe 600 Index - Imen Mahfoudh; Sameh Kobbi-Fakhfakh (Journal of Accounting and Management Information Systems (JAMIS), 2025)
Research Question- Does the mandatory adoption of International Financial Reporting Standard (IFRS) 15 "Revenue from contracts with customers” affect earnings quality? Motivation- This study adds to the empirical literature on the effects of IFRS implementation on earnings quality by examining a specific standard that addresses one of the key performance indicators i.e., Revenue. Idea- This study investigates whether the adoption of IFRS 15 is associated with changes in both accrual-based and real earnings management activities. Data- The sample consists of firms listed on the STOXX Europe 600 index. We identified 3,327 firm-year observations over the 2012- 2023 period. The study employs a difference-in-differences design. Tools- We employed a multiple regression model with panel data, including industry and year fixed effects. Estimations were carried out using STATA software. Findings- The empirical results show that the adoption of IFRS 15 did not have a statistically significant effect on either accrual-based or real earnings management. They remain robust after controlling for various determinants of earnings management and are further supported by robustness checks using entropy balancing. The findings invite standard setters to further assess whether the new revenue recognition standard, IFRS 15, has achieved its goal of enhancing financial reporting quality. Contribution- To the best of our knowledge, this is the first study to provide a comprehensive examination of both accrual-based and real earnings management in the European context, comparing the pre- and post-mandatory IFRS15 adoption periods.
Keywords: M41; M48; 650; IFRS 15; Revenue recognition; Earnings quality; Discretionary accruals; Real activities; Entropy balancing